Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1161/hypertensionaha.115.07089
|View full text |Cite
|
Sign up to set email alerts
|

SmgGDS as a Crucial Mediator of the Inhibitory Effects of Statins on Cardiac Hypertrophy and Fibrosis

Abstract: The detailed molecular mechanisms of the pleiotropic effects of statins remain to be fully elucidated. Here, we hypothesized that cardioprotective effects of statins are mediated by small GTP-binding protein GDP dissociation stimulator (SmgGDS). SmgGDS +/– and wild-type (WT) mice were treated with continuous infusion of angiotensin II (Ang II) for 2 weeks with and without oral treatment with atorvastatin or pravastatin. At 2 weeks, the extents of Ang II–induced cardiac hypertrophy and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 61 publications
2
15
0
1
Order By: Relevance
“…148 Statins decrease Rac1 levels, cardiomyocyte hypertrophy, and fibrosis in wild type mice, but not in mice that lack SmgGDS. 149 Rac1 contributes to doxorubicin-related cardiotoxicity through both a ROS-dependent and independent mechanism. 150 Finally, preoperative atorvastatin induced Rac1-mediated inhibition of NADPH in human atrial myocardium.…”
Section: Cellular Effects Of Statinsmentioning
confidence: 99%
“…148 Statins decrease Rac1 levels, cardiomyocyte hypertrophy, and fibrosis in wild type mice, but not in mice that lack SmgGDS. 149 Rac1 contributes to doxorubicin-related cardiotoxicity through both a ROS-dependent and independent mechanism. 150 Finally, preoperative atorvastatin induced Rac1-mediated inhibition of NADPH in human atrial myocardium.…”
Section: Cellular Effects Of Statinsmentioning
confidence: 99%
“…Recent studies have revealed that SmgGDS is up-regulated by statin, resulting in the nuclear transport and degradation of Rac1 (14). Additionally, SmgGDS is a crucial mediator of the inhibitory effects of statins on cardiac hypertrophy (15,16).…”
mentioning
confidence: 99%
“…При ХСН особое значение имеют плейо-тропные эффекты статинов: противовоспалительный, улучшение функции эндотелия путем усиления синтеза оксида азота, ограничение ремоделирования сердца, уменьшение оксидативного стресса [14,15]. Для больных с ХСН и сохраненной ФВ ЛЖ важна способность статинов уменьшать гипертрофию и фиброз миокарда, улучшать его диастолическую функцию [16].…”
Section: Discussionunclassified